Evaluating India’s Position in Pragmatic Clinical Trial for Public Healthcare: A Key to Real World Healthcare Solutions - Besekar, Smruti; Jogdand, Sangita; Patel, Satyawan Singh (National Journal of Community Medicine, 2024)
Pragmatic Clinical Trials (PCTs) are valuable tools for evaluating interventions in real-world settings, providing insights for clinical practice. Unlike traditional randomized controlled trial (RCTs), PCTs generate real-world evidence for better decision-making. With 615 reported globally between 1967 and 2017, a 58% increase from 2013 to 2017, India has only one registered PCT, indicating a gap in its adoption. This review examines national clinical trial registries, PubMed database for PCTs till 2024, comparing data across different nations. The study reveals a significant shortage of PCTs in India and a lack of awareness of frameworks like Pragmatic Explanatory Continuum Indicator Summary 2. India faces challenges in implementing PCTs due to low awareness, inadequate infrastructure, and logistical hurdles. However, with regulatory reforms, international collaboration, and infrastructure improvements, India can become a key player in advancing PCTs. Increased awareness and researcher training will contribute to better healthcare outcomes both domestically and globally.